Non-Scarring Alopecia in Females: A Comprehensive Review - Miguel A. Aristizabal; Alison J. Bruce; Roy S. Rogers III; Thais Pincelli (European Medical Journal Dermatology)
Alopecia is prevalent among females, categorised as either scarring or non-scarring, depending on the potential for hair follicle regeneration. Various aetiologic factors are implicated in non-scarring alopecia, including genetic predisposition, loss of immune privilege, oxidative damage, and hormonal fluctuations. Telogen effluvium, alopecia areata, and female pattern hair loss are the main causes of non-scarring alopecia in females of all ages. This review covers the aetiology, pathophysiology, and treatment of the most common non-scarring alopecias in females.